Gringo/a as Sociolinguistic Fractal - Kane, Stephanie; Manelis Klein, Harriet (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2013)
The polysemic term “gringo” inevitably mediates the negotiation of cultural identity for anthropologists carrying out fieldwork in Latin America. Drawing on experiences from the authors’ interactions in pursuit of professional goals, this analysis shows how nation, religion, gender, race, and the histories of colonization, migration, and alliance emerge and recede in kaleidoscopic encounters between hemispheric stereotypes and cross-cultural travelers. The intertwined personal experience narratives of ‘gringo-hood’ we present reveal the fractal character of knowledge and experience. This article, therefore, shows how linguistic, cultural, and especially folkloric interactions mediate the various dimensions of our socially situated experiences and the different forms of talk we encountered.